The Effect Between of Direct and Indirect Corrective Feedback on Students’ Writing Skill - syaifuddin farhan43 (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
ABSTRACT: The aim of this study was to investigate the effect of direct and indirect corrective feedback on students writing skill. Therefore, the research design applied in this study was quasi experimental research design. The researcher conducted this study at tenth grade students of SMA Islam Karangploso. The researcher used two classes as the sample. They were class X IPA and X IPS that consist of 21 students in each class. Then the researcher divided them into two groups by using small paper. Class X IPA as experimental group taught by using indirect corrective feedback and class X IPS as control group taught by using direct corrective feedback. To collect the data, pre - test and post test was used as the instruments. Then it was analysis through independent T test by using SPSS Program.          The result showed that there was significantly different score between students who were taught using direct corrective feedback and students who were taught using indirect corrective feedback. In this case, the students who were taught by using indirect corrective feedback performed more than direct corrective feedback. In this case, the mean score of experiment group was 80.48 (Sd= 6.838) and control group was 75.81 (Sd= 5.016). Through independent T test, the researcher found that the t - value was 2.522 (p= 0.016). It is lower than level of significant 0.05. It indicated that the students taught using indirect corrective feedback have better achievement in writing recount text than students taught using direct corrective feedback.            Finally, the researcher concluded that indirect corrective feedback was an effective strategy to be implemented in the writing class. It increases the knowledge of the students and gave the students such kind of awareness of errors and mistakes. Therefore, the researcher suggests English teacher to implement indirect corrective feedback on writing process. The researcher also suggest the future research who wants to conduct the similar study related to direct and indirect corrective feedback to implement this technique in different grade of the students. It is also possible to implement this technique by considering another variable such as motivation and learning style of the students. Keywords: Direct Corrective Feedback, Indirect Corrective Feedback, Writing Skill